SIKAP JIWA TOKOH UTAMA ALETTA ARKANZA DALAM NOVEL I’M A GOOD GIRL KARYA ZAHRANI SALSABILA - Maemunah, Siti (JIPIS, 2023)
This study aims to describe the mental attitude of the character Aletta Arkanza in the Novel I'm A Good Girl by Zahrani Salsabila. This study uses the study of literary psychology by utilizing Carl Gustav Jung's theory. This research is a type of qualitative research that is descriptive in nature. The source of the research data is text in the form of words or sentences that show the attitude of the character Aletta Arkanza's theory by Carl Gustav Jung. Data collection techniques in this study are using library research, reading techniques and note-taking techniques. The data in this study were analyzed using data analysis techniques by identifying, classifying, analyzing, describing, and drawing conclusions. The results of this study indicate that the attitude of the soul in the character Aletta Arkanza has two characteristics, namely introvert and extrovert. Moreover, extrovert is the most dominant data appears in this study. Keywords: Aletta Arkanza, I’m a Good Girl, Main Character, Novel, Soul Attitude